GLP-1 RA-Semaglutide a game changer drug for management of obesity with and without Diabetes - A narrative review - Islam, Quazi Tarikul; Zaman, Mir Susmita; Hasan, Mohammad Jahid (Bangladesh Journal of Medicine, 2024)
Obesity is a chronic and relapsing disease marked by excessive fat accumulation that poses serious health risks, with an increasing global prevalence including in low- and middle-income countries. Obesity-related complications, including cardiovascular diseases, diabetes, and cancer, also contribute to significant healthcare costs. Management strategies involve lifestyle modifications, pharmacological interventions, and, in severe cases, surgical procedures. Semaglutide, a GLP-1 receptor agonist, has emerged as an effective treatment for both obesity and type 2 diabetes, showing significant weight loss outcomes and improvements in metabolic health across various patient groups. However, careful monitoring of adverse effects and drug interactions is crucial for optimizing therapeutic outcomes.Several novel agents are under development, with multi-hormone receptor agonists and oral formulations likely to become available in the coming years. As effective treatment options expand, cost and availability will need to be addressed to enable equitable access to treatment. Bangladesh J Medicine 2024; 35: 133-146